Mealtime insulin BOLUS score increases prior to clinic visits in youth with type 1 diabetes. Issue 1 (14th July 2020) - McConville, Andrew; Noser, Amy E; Clements, Mark A; Patton, Susana R
Abstract : Introduction: Multiple studies confirm the occurrence of 'white coat adherence' (WCA), a term describing an increase in engagement with self-care tasks just prior to a scheduled clinic appointment, across cohorts with multiple chronic conditions. In youth with type 1 diabetes (T1D), research also shows an increase in self-monitoring blood glucose frequency ahead of youths' clinic visits. While studies show preliminary evidence for the occurrence of WCA in youth with T1D, no study has examined the effect of WCA and mealtime insulin dosing behaviors in youth with T1D. The frequency of mealtime insulin bolusing score (BOLUS) is an objective measure of mealtime insulin use in youth with T1D that could be vulnerable to WCA. To fill this gap in the literature and further our understanding of WCA in pediatric diabetes, we determined whether WCA also impacts BOLUS scores in youth with T1D. Research design and methods: We extracted insulin pump records and HbA1c levels from a clinical database for 459 youth with T1D (Mage =12.5±2.9 years). We calculated mean BOLUS scores for 6–5, 4–3, and 2–0 weeks prior to youths' routine clinic visits. We used multilevel modeling to examine patterns of BOLUS scores prior to clinic visits and tested for age differences. Results: Multilevel modeling showed a significant increase in BOLUS scores in the weeks prior to youths' clinic appointments (β=0.07, p<0.001). On average, adolescents had lower BOLUS scores than school-age children (β=−0.35, p<0.001). Post hoc analyses showed that adolescents consistently had lower BOLUS scores than children across assessments (p's<0.001). Conclusions: Youth with T1D increase their mealtime insulin use prior to clinic appointments. The BOLUS may be a viable target for intervention to drive improved glycemic control. Whether increased tendency to WCA is associated with reduced risk of diabetic complications remains to be determined.